Comparative Effectiveness of Regional Anesthesia and Nerve Block Techniques in Reducing Chronic Post-Surgical Pain in Adults Undergoing Inguinal Hernia Surgery: A Systematic Review - Gabriella, Clarisa Christina; Ida Bagus, Putu Oka Mahendra (International Medical Journal Corp. Ltd, 2024)
Background: This study to show about comparative effectiveness of regional anesthesia and nerve block techniques in reducing chronic post-surgical pain in adults undergoing inguinal hernia surgery. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: CPSP is a multifactorial and complex condition that can significantly affect the quality of life of patients undergoing surgery. General anesthesia plus ilioinguinal nerve block is better than spinal anesthesia (SA) regarding postoperative analgesia, time to mobilization and discharge, side-effect profile and satisfaction experienced by the patients. Regional block anesthesia (RBA) is superior to conventional spinal anesthesia (CSA) for pain relief at 24 hours post-surgery.